Health-related quality of life in congenital heart disease surgery patients in Pakistan: protocol for a mixed-methods study. Issue 10 (30th October 2017) - Ladak, Laila Akbar; Hasan, Babar Sultan; Gullick, Janice; Awais, Khadija; Abdullah, Ahmed; Gallagher, Robyn
Abstract : Introduction: Reduced health-related quality of life (HRQOL) has been reported in postoperative patients with congenital heart disease (CHD). However, there is a paucity of data from low-income and middle-income countries (LMIC). Differences in sociodemographics and sociocultural contexts may influence HRQOL. This protocol paper describes a study exploring HRQOL in surgical patients with CHD from a tertiary hospital in Pakistan. The study findings will assist development of strategies to improve HRQOL in a resource-constrained context. Methods and analysis: This prospective, concurrent triangulation, mixed-methods study aims to compare HRQOL of postsurgery patients with CHD with age-matched healthy siblings and to identify HRQOL predictors. A qualitative component aims to further understand HRQOL data by exploring the experiences related to CHD surgery for patients and parents. Participants include patients with CHD (a minimum of n~95) with at least 1-year postsurgery follow-up and no chromosomal abnormality, their parents and age-matched, healthy siblings. PedsQL 4.0 Generic Core Scales, PedsQL Cognitive Functioning Scale and PedsQL 3.0 Cardiac Module will measure HRQOL. Clinical/surgical data will be retrieved from patients' medical files. Student's t-test will be used to compare the difference in the means of HRQOL between CHD and siblings. Multiple regression will identify HRQOL predictors. A subsample of enrolled patients (n~20) and parents (n~20) from the quantitative arm will be engaged in semistructured qualitative interviews, which will be analysed using directed content analysis. Anticipated challenges include patient recruitment due to irregular follow-up compliance. Translation of data collection tools to the Urdu language and back-translation of interviews increases the study complexity. Ethics and dissemination: Ethics approval has been obtained from The Aga Khan University, Pakistan (3737-Ped-ERC-15). Study findings will be published in peer-reviewed journals and presented at national and international conferences.